2022
DOI: 10.1038/s41598-021-04079-w
|View full text |Cite
|
Sign up to set email alerts
|

Cortical diurnal rhythms remain intact with microglial depletion

Abstract: Microglia are subject to change in tandem with the endogenously generated biological oscillations known as our circadian rhythm. Studies have shown microglia harbor an intrinsic molecular clock which regulates diurnal changes in morphology and influences inflammatory responses. In the adult brain, microglia play an important role in the regulation of condensed extracellular matrix structures called perineuronal nets (PNNs), and it has been suggested that PNNs are also regulated in a circadian and diurnal manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
(62 reference statements)
1
17
0
1
Order By: Relevance
“…It is possible that neuroinflammation mediates the histochemical “loss” of WFA + PNNs by influencing the PNN CS-GAG composition and reducing the abundance of WFA-recognized CS-O (0S) unit. This possibility aligns with studies that show that microglia inhibition results in increased WFA + PNN histology in normal mice (Liu et al, 2021 ; Barahona et al, 2022 ), although whether this effect also associates with changes in the CS-GAG composition remains unknown.…”
Section: Re-evaluation Of Pnn “Loss” By Wfa Labelingsupporting
confidence: 86%
See 2 more Smart Citations
“…It is possible that neuroinflammation mediates the histochemical “loss” of WFA + PNNs by influencing the PNN CS-GAG composition and reducing the abundance of WFA-recognized CS-O (0S) unit. This possibility aligns with studies that show that microglia inhibition results in increased WFA + PNN histology in normal mice (Liu et al, 2021 ; Barahona et al, 2022 ), although whether this effect also associates with changes in the CS-GAG composition remains unknown.…”
Section: Re-evaluation Of Pnn “Loss” By Wfa Labelingsupporting
confidence: 86%
“…Importantly, restoration of WFA + PNNs through PLX5622-driven inhibition of microgliosis also occurred independently to changes in Aβ plaque load (notably, pTau expression was not analyzed) (Crapser et al, 2020 ). Although it remains unclear whether microglia inhibition in 5xFAD and 3xTg-AD mice restores PNNs to that of wild-type control levels, the outcomes of these studies nevertheless complement recent discoveries that microglia play critical roles in daily PNN maintenance and turnover, since inhibition of microglia in normal mouse brain also increases WFA + PNN abundance (Liu et al, 2021 ; Barahona et al, 2022 ).…”
Section: Evidence Linking Changes In Perineuronal Nets With Alzheimer...mentioning
confidence: 75%
See 1 more Smart Citation
“…We observed no changes in sleep during weeks 2 or 3 of the depletion period in mice with depleted microglia and nominal changes in sleep during the repopulation period, which strongly indicates that microglia do not play a critical role in regulating sleep under non-inflammatory conditions. Although no study to date has investigated sleep during the depletion of microglia, previous research has demonstrated that microglia do not play a role in the maintenance of diurnal rhythms [ 96 ]. In the absence of microglia during PLX treatment, cortical diurnal gene expression remains unchanged compared to mice on the control diet [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considered together, these findings suggest that microglia may play a key role in diurnal rhythm generation since its ablation leads to the concomitant disruption of diurnal profiles and to the dysregulation of the expression of certain clock genes in different brain domains. In contrast, Barahona and collaborators showed that, in the cortex, ablation of microglia did not affect the rhythmical pattern of clock genes expression, since in Cx3cr1-Dtr rats clock genes all maintained their diurnal rhythmical expression (Barahona et al, 2022). Due to these conflicting data, further studies on this glia population are required to elucidate its role in the generation of rhythms throughout the brain.…”
Section: Microglia: the Rhythmicity Around Immune And Inflammatory Re...mentioning
confidence: 95%